Minimum legal drinking age and the social gradient in binge drinking - Alexander Ahammer; Stefan Bauernschuster; Martin Halla; Hannah Lachenmaier (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
Low minimum legal drinking ages (MLDAs), as prevalent in many European countries, are severely understudied. We use rich survey and administrative data to estimate the impact of the Austrian MLDA of 16 on teenage drinking behavior and morbidity. Regression discontinuity estimates show that legal access to alcohol increases the frequency and intensity of drinking, which results in more hospital admissions due to alcohol intoxication. The effects are stronger for boys and teenagers with low socioeconomic background. Evidence suggests that the policy's impact can hardly be fully explained by access. Data from an annual large-scale field study shows that about 25 percent of all retailers sell even hard liquor to underage customers. More generally, perceived access to alcohol is very high and hardly changes at the MLDA. However, teenagers consider binge drinking at weekends to be less harmful after gaining legal access.
Keywords: I12; I18; H75; J13; 330; Alcohol; minimum legal drinking age; morbidity